Gambaran Kualitas Pelayanan Petugas Donor Darah di Unit Transfusi Darah PMI Kabupaten Bantul - Arlinda, Elyn (Jurnal Indonesia Sehat, 2024)
Background:  The Blood Transfusion Unit (UTD) provides blood services such as blood donation, supply, distribution to maintain blood availability. However, the availability of blood can also be reduced due to less interest from donors. WHO states that the need for blood bags for each country is 2% of the total population. Indonesia with a total population of 277.75 million in 2023 data shows that the stock of bags is only 77,438 which means it is very lacking. The shortage of blood bags is due to low interest in blood donation. One of the things that influence interest in blood donation is the quality of service.  The purpose of this study was to determine the description of service quality at UDD PMI Bantul Regency. Methods: This study uses quantitative methods with descriptive analysis design using questionnaire instruments including tangible aspects, 4 questions on reliability aspects, 3 questions on responsiveness aspects, 4 questions on assurance aspects and 3 questions on empathy aspects and using a Likert scale. Results: Shows that the quality of service of blood donor officers at UTD PMI Kab. Bantul shows that the quality of service in the Tangible aspect shows that the quality of service is very good (65.6%), the Reliability aspect shows that the quality of service is very good (65.6%), the responsiveness aspect shows that the quality of service is very good (59.4%), the Assurance aspect of respondents shows that the quality of service is very good (68.8%) and the empathy aspect shows that the quality of service of donor officers is very good (53.1%). Conclusion: the quality of service of blood donor officers at UTD PMI Kab. Bantul from the five aspects is very good.